2015
DOI: 10.1016/j.jct.2015.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Phase equilibrium measurements for clathrate hydrates of flue gas (CO2+N2+O2) in the presence of tetra-n-butyl ammonium bromide or tri-n-butylphosphine oxide

Abstract: Please cite this article as: J. Du, L. Wang, Phase equilibrium measurements for clathrate hydrates of flue gas (CO 2 + N 2 + O 2 ) in the presence of tetra-n-butyl ammonium bromide or tri-n-butylphosphine oxide, J. Chem. Thermodynamics (2015), doi: http://dx.doi.org/10. 1016/j.jct.2015.04.023 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typeset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It has been suggested 31 that several hydrates can be formed in the system, and TBPO•28H 2 O was previously reported as their averaged composition. Most recently reported data on P, T hydrate phase equilibria for aqueous solutions of TBPO + CH 4 , 32,33 + CO 2 , 32,33 + N 2 , 33 + H 2 , 32 + simulated biogas (60 mol % CH 4 + 40 mol % CO 2 ), 34 + simulated mine ventilation air (0.5 vol % CH 4 + 99.5 vol % air), 35 + simulated flue gas (12.5 vol % CO 2 + 80.5 vol % N 2 + 6.9 vol % O 2 ) 36 showed a shift of the hydrate phase equilibria to lower pressures and higher temperatures, compared to the corresponding gas + water system. These observations are evidence of the inclusion of gas molecules into the cavities of the TBPO hydrate structure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been suggested 31 that several hydrates can be formed in the system, and TBPO•28H 2 O was previously reported as their averaged composition. Most recently reported data on P, T hydrate phase equilibria for aqueous solutions of TBPO + CH 4 , 32,33 + CO 2 , 32,33 + N 2 , 33 + H 2 , 32 + simulated biogas (60 mol % CH 4 + 40 mol % CO 2 ), 34 + simulated mine ventilation air (0.5 vol % CH 4 + 99.5 vol % air), 35 + simulated flue gas (12.5 vol % CO 2 + 80.5 vol % N 2 + 6.9 vol % O 2 ) 36 showed a shift of the hydrate phase equilibria to lower pressures and higher temperatures, compared to the corresponding gas + water system. These observations are evidence of the inclusion of gas molecules into the cavities of the TBPO hydrate structure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They concluded that TBPO at 5 wt % exhibits a stronger promotion effect at all temperatures examined, while the case of 26 wt % TBPO performs better for temperatures above 287 K. Additional details for the conditions of the experimental measurements are reported in Tables S2a and b of the Supporting Information. Figure 4 also shows the experimental data of Du and Wang 96 for the ternary mixture, as well as the experimental data of Lee et al 59 and Sun et al 62 for the case of the binary mixture CO 2 + N 2 with a composition of 10 and 90 vol %, respectively (i.e., lumping the amounts of N 2 and O 2 ), which are the closest available binary mixtures to the ternary studied by Du and Wang. 96 Given the scarcity of the experimental data, especially for the ternary system, we recommend that additional measurements should be performed for the ternary case.…”
Section: Presentation and Discussion Of Thementioning
confidence: 92%
“…Figure 4 also shows the experimental data of Du and Wang 96 for the ternary mixture, as well as the experimental data of Lee et al 59 and Sun et al 62 for the case of the binary mixture CO 2 + N 2 with a composition of 10 and 90 vol %, respectively (i.e., lumping the amounts of N 2 and O 2 ), which are the closest available binary mixtures to the ternary studied by Du and Wang. 96 Given the scarcity of the experimental data, especially for the ternary system, we recommend that additional measurements should be performed for the ternary case. From the above discussion, it is evident that for the particular system (GM-2) there is plenty of room for future experimental and computational studies, especially if strong evidence becomes available for the need to perform delumping of N 2 and O 2 in the analysis.…”
Section: Presentation and Discussion Of Thementioning
confidence: 92%
See 1 more Smart Citation